Risk Factors Associated with Impaired Ovarian Reserve in Young Women of Reproductive Age with Crohn’s Disease - Zhao, Yue (Intest Res, 2020)
BACKGROUND/AIMS: Crohn’s disease (CD) primarily affects young female adults of reproductive age. Few studies have been conducted on this population’s ovarian reserve status. The aim of study was to investigate potential risk factors associated with low ovarian reserve, as reflected by serum anti-Müllerian hormone (AMH) in women of reproductive age with CD. METHODS: This was a case-control study. Cases included 87 patients with established CD, and healthy controls were matched by age, height and weight in a 1:1 ratio. Serum AMH levels were measured by enzyme-linked immunosorbent assay. RESULTS: The average serum AMH level was significantly lower in CD patients than in control group (2.47±2.08 ng/mL vs. 3.87±1.96 ng/mL, respectively, P<0.001). Serum AMH levels were comparable between CD patients and control group under 25 years of age (4.41±1.52 ng/mL vs. 3.49±2.10 ng/mL, P=0.06), however, serum AMH levels were significantly lower in CD patients over 25 years of age compared to control group (P<0.05). Multivariable analysis showed that an age greater than 25 (odds ratio [OR], 10.03; 95% confidence interval [CI], 1.90–52.93, P=0.007), active disease state (OR, 27.99; 95% CI, 6.13–127.95, P<0.001) and thalidomide use (OR, 15.66; 95% CI, 2.22–110.65, P=0.006) were independent risk factors associated with low ovarian reserve (serum AMH levels <2 ng/mL) in CD patients. CONCLUSIONS: Ovarian reserve is impaired in young women of reproductive age with CD. Age over 25 and an active disease state were both independently associated with low ovarian reserve. Thalidomide use could result in impaired ovarian reserve.